Comparative Analysis of U.S. and Chinese Strategic Cultures - Asya Gasparyan (China Quarterly of International Strategic Studies)
Understanding the strategic mindset of the United States and China is essential, as their military behavior has significant global implications. The study employs a cultural approach to examine how historical, geographical, and ideological factors shape their strategic-military decisions. By addressing the central research question: how do the strategic cultures of the United States and China influence their preferences for using military force? This paper seeks to reveal the main differences in American and Chinese approaches to the use of military force. The time frame of analysis is limited to the 21st century, a period marked by China’s undeniable rise as a global power and the renewed significance of cultural theorizing in international relations scholarship. The findings underscore that the ideological underpinnings and operational behavior of both superpowers are pivotal in shaping their security perceptions and influencing patterns of military force application. By examining these elements, this study aims to enhance our understanding of how the distinct strategic mindsets of these superpowers impact their interactions on the global stage and inform their responses to various security challenges.